Role of Cardiac MRI Including LGE, T1 and T2 Mapping in the Assessment of Cardiac Involvement in Patients of Nonspecific Aorto-arteritis: A Prospective Study - Chandrashekhara, S H.; Gulati, Gurpreet Singh; Sharma, Sanjiv; Kumar, Sanjeev; Chaudhary, Shiv Kumar; Jagia, Priya; Seth, Sandeep; Gupta, Saurabh Kumar; Khan, Mahroof (Indian Journal of Radiology and Imaging, 2022)
Objective Nonspecific aorto-arteritis (NSAA) may involve the myocardium in the form of edema and fibrosis. We conducted this study to investigate role of cardiac MRI including late gadolinium enhancement (LGE), T1 and T2 mapping in the assessment of cardiac involvement in NSAA.Methods and Materials Over the period between 2016 and 2019, 36 patients with NSAA presenting with uncontrolled hypertension, left ventricular dysfunction, congestive cardiac failure, or tachyarrhythmia were included in the study. We also had 16 voluntary control patients for providing normal T1 and T2 mapping values.Results The average age of patients was 27.1 years and the majority were females. MRI is more sensitive than echocardiography in the detection of LV dysfunction and RWMA. Out of 36 patients, 10 (27.8%) had LGE. The most common pattern of midmyocardial enhancement was present in 5 out of 10 patients. Five (13.8%) patients show mid-myocardial enhancement, followed by epicardial enhancement, which was seen in four (11.11%) patients. The values of post-gad T1 mapping values were significantly lower than pre-gad T1 mapping values. At a cut-off global native T1 mapping value of 1019 milliseconds had the sensitivity of 83.3% and specificity of 81.2% in detecting an abnormal T1 map. No significant association of MRI contrast enhancement with elevated ESR and CRP levels. There was no significant relation of myocardial T2 mapping values between NSAA and control groups.Conclusion Quantitative tissue characterization in the myocardium with native T1 mapping values help in the detection of cardiac involvement in patients with NSAA. T1 mapping may provide incremental value in the assessment of myocardial involvement in NSAA in addition to LGE imaging.
Keywords: cardiac MRI; nonspecific aorto-arteritis; T1 mapping; T2 mapping